Mathematics education and subjectivity cultures and cultural renewal - Brown, Tony 1946-; SpringerLink (Online service). (Dordrecht Netherlands Springer, 2011)
This book rethinks mathematical teaching and learning with view to changing them to meet or resist emerging demands. Through considering how teachers, students and researchers make sense of their worlds, the book explores how some linguistic and socio-cultural locations link to prevalent conceptions of mathematics education. The locations include classroom mathematics, spatial awareness, media images of mathematics, curriculum development, teacher education and mathematics education research itself. The book introduces cutting edge theories of subjectivity that trouble more familiar psychological theories of humans apprehending mathematical concepts. Rather, it suggests that our senses of self and of mathematics result from self-reflections within the various localities in which we live. In foregrounding subjectivity the book shows how mathematics can provoke alternative ways of thinking towards enlivening our transformative capacities. Learning itself is depicted as participation in cultural renewal, where the very mathematics encountered is becoming something new. Addressing teachers, teacher educators and researchers, the book invites the reader to contemplate alternative trajectories of change into fresh ways of being.
About the author. - Acknowledgements. - 1 Introduction. 2 The regulation of spatial perception.- 3 Cultural mediation of mathematics.- 4 Teacher conceptions of curriculum. 5 Subjectivity in mathematics education research.- 6 Lacanian subject of mathematical learning.- 7 The cultural renewal of mathematical learning.- 8 The political shaping of mathematical learning.- 9 Concluding remarks.- References.- Index.
Electronic reproduction.
Keywords: Mathematics -- Study and teaching; Electronic books